Analysis of the Effect of Current Ratio, Working Capital, Debt Ratio on the Performance of Various Industrial Companies Listed on the IDX - Refni sukmadewi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
The purpose of this study is to prove the effect of financial ratios Current Ratio, Working Capital Debt Ratio on the performance of various industrial companies as measured by profits variables on company performance.The object of research is the various industrial sector companies operating in Indonesia in 2017-2019. The sampling technique in this study used a purposive sampling technique, namely the selection of sampling based on certain criteria. The analysis technique used is multiple regression analysis. To determine the accuracy of the model, it is necessary to test several classical assumptions that underlie the regression model. Classical assumption tests used in this study include tests, normality, multicollinearity, heteroscedasticity and autocorrelation. The results partially show that current ratio and debt ratio has a significant effect on performance, while working capital has no significant effect on performance. Simultaneously current ratio, working capital and debt ratio have a significant effect on profitability.